Monovalent cation transporters at the plasma membrane in yeasts - Ariño, Joaquín; Ramos, José; Sychrova, Hana (Yeast (Chichester, England), 2019)
Maintenance of proper intracellular concentrations of monovalent cations, mainly sodium and potassium, is a requirement for survival of any cell. In the budding yeast Saccharomyces cerevisiae, monovalent cation homeostasis is determined by the active extrusion of protons through the Pma1 H+ -ATPase (reviewed in another chapter of this issue), the influx and efflux of these cations through the plasma membrane transporters (reviewed in this chapter), and the sequestration of toxic cations into the vacuoles. Here, we will describe the structure, function, and regulation of the plasma membrane transporters Trk1, Trk2, Tok1, Nha1, and Ena1, which play a key role in maintaining physiological intracellular concentrations of Na+ , K+ , and H+ , both under normal growth conditions and in response to stress.
Keywords: kationty jednomocné; Cation Transport Proteins; Nha1 antiporter; Sodium; homeostáza; cation homeostasis; regulace genové exprese u hub; Sodium-Potassium-Exchanging ATPase; sodík; plasma membrane transport; buněčná membrána; Saccharomyces cerevisiae Proteins; Cations, Monovalent; yeasts; proteiny přenášející kationty; Tok1; Potassium; Ena1 ATPase; Trk potassium transporters; Ion Transport; Gene Expression Regulation, Fungal; iontový transport; draslíkové kanály; protonové ATPasy; draslík; Cell Membrane; Saccharomyces cerevisiae; Homeostasis; Proton-Translocating ATPases; Na(+)-H(+) antiport; Saccharomyces cerevisiae - proteiny; Potassium Channels; Sodium-Hydrogen Exchangers; sodíko-draslíková ATPasa